Feasibility Study of a Competency-Based Performance Assessment Instrument for General Practitioners - Samdani, Annisa Fasichatul Laila; Arini, Merita; Basha, Muzaitul Akma Binti Mustapa Kamal (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2026)
An objective and standardized performance evaluation instrument is essential to ensure that general practitioners deliver services in accordance with professional competency standards. This study aims to evaluate the feasibility of a competency-based performance assessment instrument using the Analysis–Design–Develop (ADD) model and multiple regression analysis. The regression model met all classical statistical assumptions. Emphasizing the overall model rather than partial effects, the results demonstrated a significant overall feasibility of the instrument (F = 8.115; p < 0.05) when integrating the six competency domains: patient care, medical/clinical knowledge, practice-based learning and improvement, interpersonal and communication skills, professionalism, and system-based practice were confirmed as feasible components of the instrument. These findings indicate that the instrument is appropriate for use in healthcare facilities and can support a comprehensive and objective evaluation of general practitioner performance.